Paradise lost : a primer - Cavanagh, Michael (The Catholic University of America Press, 2020)
"A record of a teacher's lifelong love affair with the beauty, wit, and profundity of Paradise Lost, celebrating John Milton's un-doctrinal, complex, and therefore deeply satisfying perception of the human condition. After surveying Milton's recurrent struggle as a reconciler of conflicting ideals, this primer undertakes a book-by-book reading of Paradise Lost, reviewing key features of Milton's "various style," and why we treasure that style. Cavanagh constantly revisits Milton the singer and maker, and the artistic problems he faced in writing this almost impossible poem. This book is emphatically for first-time readers of Milton, with little or no prior exposure, but with ambition to encounter challenging poetry. These are readers who tell you they "have always been meaning to read Paradise Lost," who seek to enjoy the epic without being overwhelmed by its daunting learning and expansive frame of reference. Avoiding the narrowly specialized focus of most Milton scholarship, Cavanagh deals forthrightly with issues that recur across generations of readers, gathering selected voices--from scholars and poets alike--from 1674 through the present. Lively and jargon-free, this primer makes Paradise Lost accessible and fresh, offering a credible beginning to what is a great intellectual and aesthetic adventure"--Publisher's description